Devising a method for complex steganographic embedding of information in the structural-psychovisual space - Barannik, Vladimir; Barannik, Dmitry; Babenko, Mykhailo; Prokopenko, Rodion; Akimov, Oleksandr; Petrukha, Nina (Eastern-European Journal of Enterprise Technologies, 2026)
This study examines the set of processes aimed at improving the efficiency of steganographic methods for information protection, while ensuring a specified level of integrity and timeliness of transmission in infocommunication systems. The work addresses a scientific and applied task of increasing the level of information security while maintaining a specified level of integrity and timely delivery of data from unmanned aerial systems (UASs). It relates to the existence of a contradiction between ensuring the confidentiality of video information and the efficiency of its delivery with a given integrity. In the process of research, a method for structural steganographic embedding has been devised, based on changing the values of positional basis (PB). The difference is the embedding of information in the process of modifying the PB values, taking into account the detection of structural dependences in the spectrally modified space of a video container (VC). Such transformations are carried out under conditions of reducing the influence of spectral space modifications on the compression level. The above advantages make it possible to build a comprehensive method of steganographic transformations in the process of VC compression. The method is distinguished by two principal aspects. The first is the use of a sequence of steganographic transformations in independent spaces to detect dependences that are used in the process of embedding information. The second is that information is embedded in the structural-spectral space, taking into account its modification by the youngest bits. This enables increasing the level of steganographic capacity by an average of 7% without distorting the integrity of the stegano-containers and removing hidden information on the receiving side. The devised method is intended to be used to improve the confidentiality, efficiency, and integrity of video information delivery from unmanned systems